CERITA RAKYAT JERMAN PERSPEKTIF PSIKOLOGI JUNGIAN [Folklore German Perspective Jungian Psychology] - Anas Ahmadi (Kantor Bahasa Provinsi Maluku, 2016)
This article presented about German folktale that studied through the perspective of Jungian psychoanalyst. This study used the theory of archetypes, archetype to dissect patterns of women in the German folktale (written by Grimmm brothers). The Qualitative study used book Tales of Germany (2011) as the data source which had published/translated by Elex Media Komputindo. The result showed that the pattern archetype of women in fairy tale brothers Grimm macro/major was divided into two, they were(1) archetype female sacral (sacred) and (2) archetype of women profane (profane. The micro/specific archetype female sacral include (1) good mother/wife/ grandma, and (2) good women /girls . the archetype of women profane include (1) the witch, (2) stepmother, (3) the greedy wife, (4) dumb women, ( 5) maids, and (6) /girl. If it is related with the archetype arch, archetype in the Grimm brothers' fairy tale reffered to Athens, Hestia, Artemis, Hecate, Hera, Aphrodite and Psyche. Artikel ini memaparkan tentang cerita rakyat jerman yang dikaji melalui perspektif psikoanalis Jungian. Penelitian ini menggunakan teori archetype untuk membedah pola archetype perempuan dalam cerita rakyat Jerman (yang ditulis oleh Grimmm bersaudara). Penelitian berpendekatan kualitatif ini menggunakan sumber data buku Dongeng Jerman (2011) yang diterbitkan/diterjemahkan oleh Elex Media Komputindo. Hasil temuan menunjukkan bahwa pola archetype perempuan dalam dongeng Grimm bersaudara secara makro/utama terbagi menjadi dua, yakni (1) archetype perempuan sakral (sacred) dan (2) archetype perempuan profan (profane. Secara mikro/spesifik archetype perempuan sakral meliputi (1) ibu/istri/nenek yang baik, dan (2) putri/gadis yang baik. Adapun archetype perempuan profan meliputi (1) ibu/nenek penyihir, (2) ibu tiri, (3) istri serakah, (4) perempuan dungu, (5) dayang, dan (6) putri/gadis. Jika dikaitkan dengan archetype arch, archetype dalam dongeng Grimm bersaudara mengarah pada Athena, Hestia, Artemis, Hecate, Hera, Aphrodite, dan Psyche.